PRIORITAS RESIKO KERJA PEMBUATAN KUSEN PINTU (STUDI KASUS: PD. SUMBER PUTRI REJEKI, TANGERANG) - Ratih Wulandari; Ardhy Lazuardy (Asosiasi Dosen Muda Indonesia, 2024)
PD Sumber Putri Rejeki is a trading company which operates in the sector of making door frames, door panels, glass windows, etc. located in the Tangerang Regency area. The process of making door frames involves various processes such as unloading wood, cutting wood, making profiles, smoothing, assembling and finishing the product, namely varnishing. Where every stage in production has a potential risk of work accidents which need to be evaluated and managed effectively. Work accidents can have a serious impact on the health and productivity of workers, as well as creating inconvenience and losses for the company. Based on these problems, the aim of this research is to determine the risk priority number (RPN), which is a risk priority number obtained from multiplying severity, occurrence and detection using the FMEA (Failure Mode Effect Analysis) method as a risk analysis tool. The conclusion of this research is that the potential dangers that exist in PD Sumber Putri Rejeki are injured hands, injured feet, shoulder injuries, cut limbs, respiratory problems and vision problems. The average potential hazard value with the highest level of risk is cutting work with an RPN value of 74, while the description of the potential hazard for all jobs is visual impairment due to material residue in contact with the eyes with an RPN value of 108.